Majestic descending - Graham, Mitchell (Forge, 2007)
Katherine Adams is taking a cruise on the fabulous Ocean Majestic, the largest and most luxurious ocean liner in the world. This is exactly the break Katherine needs from her demanding Atlanta legal practice. On board, she meets John Delaney, a streetwise ex-NYPD detective who is now a lawyer. Romance is in the air, but all is not quite right aboard the Majestic. Events soon turn the romantic dream into a grisly nightmare. After Katherine and Delany narrowly escape from a disaster of terrifying proportions, she must quickly learn how to survive in the dark world of international conspiracy and terrorism. From the blood-smeared decks of the Majestic to the beautiful and dangerous countryside of Italy, to the streets of New York, Katherine finds herself in a desperate race against a ruthless hit man. And, unless she and Delany can unmask the sinister cabal behind the killing, she will become his next victim.--From publisher description.